Performance analysis of shapeable-maximum power point tracking technique from thermoelectric-solar hybrid energy harvesting sources on mobile devices - Md Yusop, Azdiana; Mohamed, Ramizi; Sulaiman, Noor Asyikin; Mohd Isira, Ahmad Sadhiqin (Taylor & Francis Group, LLC, 2025)
In this study, the performance analysis of the thermoelectric-solar (TEM-SA) hybrid energy harvesting system is presented. The proposed system is analyzed for continuous and discontinuous load condition and mobile devices as a load. In this feed forward type of controller, Inverse Dynamic Analysis Input Shaper (IDAIS) is introduced to shape the unsteady response behavior to become stable input and is named as Shapeable MPPT (SMPPT). The experimental analysis is done to verify the performance of the new arrangement proposed circuit of HEHS which is used only one MPPT board. An initial test is made in determining which energy-efficient sources are capable to produce the highest output. Then the device that produces the highest output is connected to the new arrangement proposed circuit incorporated SMPPT unit, the converter, and the energy storage. With constant source supply, full charging time obtained for mobile phone is 4 hours and 30 minutes which is equivalent to the charging period using the normal alternating current sources. Greater focus is then given to the charging time for some types of mobile phones that have different battery capacity mAH. From the verification results, it is found that the load that having lowest mAh values steadily able to reach the full charging period faster than the others.